The role of novel structural systems in sustainable architecture: Tronco system - Omid Bamshad; zahra maleki; Alireza Habibi; Sheyda Salehi (مهندسی و مدیریت ساخت)
One of the solutions for architecture sustainable development is industrial implementation of buildings systems with sustainable architecture principles. Industrialization is increasing the use of human resources, raw materials and capital in order to respond to the housing needs of the society and economic productivity by using new and sustainable technologies that are organized and coherent in a regular and modular structure. Today, with the development in the construction industry and the ever-increasing need to buildings, we need solutions with the goal of sustainable architecture planning, management and coordinated growth of related industries. In this research, the introduction of Tronco system, its construction method and technical specifications including structural elements, architectural features, safety and its strengths and weaknesses have been discussed. With regard to sustainable urban development, it can be concluded that the Tronco system has the ability to become a sustainable system. Also, this system has a favorable level of energy consumption optimization and brings sustainable development in architecture.